Асоцијации меѓу прекумерна тежина и обезност со дефициенција на витамин Д кај школските деца на Косово - Кека Силај, Алије (Медицински факултет, УКИМ, Скопје, 2018)
BACKGROUND AND OBJECTIVES: Obesity among children and adults has emerged as one of the most serious public health concerns in the 21st century. As with obesity, vitamin D deficiency is reaching epidemic proportions worldwide, in both pediatric and adult populations. Overweight children have increased the incidence of earlier onset of many disease processes and deficiency of vitamin D is considered as a potential risk factor for their manifestation. This study aimed to assess the prevalence of childhood overweight and obesity in a group of Kosovo schoolchildren, also to find the correlation between BMI and other anthropometric variables, in particular to determine the association of childhood obesity with serum 25-hydroxyvitamin D [25(OH)D] concentration. To our best knowledge, this is the first study to investigate the association between obesity and vitamin D status in children with overweight and obesity in our country. METHODS AND STUDY DESIGN: This is a cross-sectional study that firstly has involved 500 Albanian school children aged 9–13 years, in one primary public school of the capital city of Kosovo, performed during 2014. Subsequently, during the systematic visits performed in spring 2016 in different primary schools in the capital city of Kosovo, children that resulted to be with overweight and obesity were invited to participate for further evaluation. In total 130 children responded positively. All these children were subjected to completing the survey on possible causes of obesity, as well as clinical and laboratory examinations. The evaluation was performed in the University Clinical Centre of Kosovo-Pediatric Clinic, Department of Endocrinology. RESULTS: From 500 children aged 9 to 13 years old, included in our research 49.4% was boys, 50.6% girls. Based on BMI the prevalence of overweight, obesity were 15.2%, 10.6%, respectively. The boys were more often overweight and obese compared to girls (Male 62.3% vs. 34.9%). Meanwhile, according to waist circumference and waist to height ratio (WHtR) with central obesity were 19.0 %, 23%, respectively. Moreover, based on WHtR, a higher percent of central obesity, 47.9% was found in girls compared with 25.9% boys. Furthermore, we have gained a significant positive correlation between BMI and waist circumference, likewise, a significant positive correlation to a large degree between BMI and skinfold thickness (triceps and suprailiac). Further, from 130 children with overweight and obesity, which were investigated for clinical and laboratory examination, overweight and obese were 33.8% and 66.1%, respectively. The vitamin D deficiency (<20 ng/ml) was present at 103 (79.2%) children, 23 (17.7%) had insufficient (20-30 ng/ml) while only four children had normal level (30-100 ng/ml). Vitamin D deficiency significantly was more often in children with obesity than in children with overweight. Furthermore, with an increase of BMI for one unit of measure, the concentration of vitamin D was reduced by an average of 0.839 ng/ml. Meanwhile, the positive significant correlations of BMI with triglycerides, cholesterol, and glycemia were found. The BMI of mothers, their level of education, the way of feeding of children during the first year of life, as well as further nutrition habits had a significant relation with the BMI of children. CONCLUSION: According to our research, and comparison with other studies, we found a quite similar prevalence of overweight/obesity in this age of children. BMI correlates with other anthropometric variables important for detecting childhood overweight and obesity. Children with overweight and obesity had the high prevalence of vitamin D insufficiency, which suggests us that routinely screening for and treating vitamin D deficiency, in these children, should be considered.
Докторска дисертација одбранета во 2018 година на Медицинскиот факултет во Скопје, под менторство на проф. д–р Даниела Миладинова.
Keywords: children, overweight, obesity, vitamin D insufficiency